2018
DOI: 10.1038/s41467-018-03884-8
|View full text |Cite
|
Sign up to set email alerts
|

BRI1 and BAK1 interact with G proteins and regulate sugar-responsive growth and development in Arabidopsis

Abstract: Sugars function as signal molecules to regulate growth, development, and gene expression in plants, yeasts, and animals. A coordination of sugar availability with phytohormone signals is crucial for plant growth and development. The molecular link between sugar availability and hormone-dependent plant growth are largely unknown. Here we report that BRI1 and BAK1 are involved in sugar-responsive growth and development. Glucose influences the physical interactions and phosphorylations of BRI1 and BAK1 in a conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 69 publications
0
51
0
Order By: Relevance
“…Glucose acts as a primary carbon and energy source in plants and plays a crucial role in plant growth, development, and physiology by coordinating with phytohormone signals. Enhanced production of glucose leads to manipulation of root architecture for maximum development through interactions with auxin metabolism genes (Li et al, ; Moore et al, ; Peng et al, ). Furthermore, increased concentration of UDP‐glucose leads to accumulation of higher biomass in plants and helps in vegetative phase change by repressing the miR156A/miR156C (Christopher, Rensburg, & Ende, ; Yang, Xu, Koo, He, & Poethig, ).…”
Section: Discussionmentioning
confidence: 99%
“…Glucose acts as a primary carbon and energy source in plants and plays a crucial role in plant growth, development, and physiology by coordinating with phytohormone signals. Enhanced production of glucose leads to manipulation of root architecture for maximum development through interactions with auxin metabolism genes (Li et al, ; Moore et al, ; Peng et al, ). Furthermore, increased concentration of UDP‐glucose leads to accumulation of higher biomass in plants and helps in vegetative phase change by repressing the miR156A/miR156C (Christopher, Rensburg, & Ende, ; Yang, Xu, Koo, He, & Poethig, ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike animals, plant genomes encode few GPCRs, and plant Gα could be self‐activated (Johnston et al ; Urano et al ; Bradford et al ; Pandey and Vijayakumar ), suggesting that plant G proteins sense signals in different ways from those of animals. Several studies implied that receptor‐like kinases (RLKs) are potential factors that percept and transduce signals to G proteins (Lease et al ; Llorente et al ; Bommert et al ; Liu et al ; Ishida et al ; Aranda‐Sicilia et al ; Choudhury and Pandey ; Liang et al ; Yu et al ; Peng et al ). Plant genomes encode hundreds of RLKs, which are single‐transmembrane proteins (De Smet et al ).…”
Section: The Potential Mechanisms Of G Proteins In Sensing Upstream Smentioning
confidence: 99%
“…Notably, tyrosine phosphorylation is also essential for BAK1 function in immune signaling (Perraki et al , ). BAK1 is a co‐receptor for many LRR‐RKs and functions in plant immunity, growth, and development (de Oliveira et al , ; Yamada et al , ; Peng et al , ; Zhou et al , ). A recent study showed that Y403 phosphorylation is required for BAK1 function in immune signaling, highlighting the importance of tyrosine phosphorylation for this immune protein (Perraki et al , ).…”
Section: Discussionmentioning
confidence: 99%